Artificial Ripening and Seed Maturity in Silver Fir (Abies pindrow Spach) - Singh, Ombir; Lalhal, J . S.; Prasad, Bhagwati (Indian Forester, 1996)
The paper presents the result of artificial ripening and seed maturity in silver fir (Abies pindrow Spach).